Management of a facial partial thickness chemical burn in a dog caused by bleach. Issue 2 (24th January 2017) - Kawalilak, Lukas T.; Fransson, Boel A.; Alessio, Terri L.
Abstract: Objective: To describe the management and successful outcome of a late‐recognition partial thickness bleach burn to the face and corneas of a dog. Case Summary: A 1‐year‐old male neutered Fox Terrier mix breed dog was evaluated for sloughing facial epithelium 5 days after coming into contact with an 8.25% household bleach cleaning solution. Severe erythema, edema, and crusting were noted around the muzzle and margins of both eyes, with moderate to severe alopecia in these areas. A partially detached, partial thickness eschar was present on the muzzle, while a firmly attached eschar was present in the region of both frontal sinuses. These injuries were consistent with a focal, superficial, and partial thickness chemical burn. Multiple ocular abnormalities, the most concerning of which was corneal ulceration, were also present. The patient's wounds were managed conservatively with limited surgical debridement of the affected epithelium 11 and 22 days after the initial exposure. Topical ocular medications, corneal debridement, and a superficial keratectomy were also used. All lesions resolved completely by 84 days postexposure, with no residual effects on the patient's quality of life. New Information: Chemical burns caused by contact with alkaline agents such as bleach (sodium hypochlorite) result in extensive necrosis of the skin and underlying structures. This is the first report of management alkaline facial burns in a dog. If inadequate or delayed hydrotherapy following exposure has resulted in superficial partial thickness burns, conservative management can be successful when traditional treatments, especially bandaging, are not feasible.